1997
DOI: 10.1002/(sici)1098-2744(199708)19:4<225::aid-mc2>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Matrilysin gene expression in sporadic and familial colorectal adenomas

Abstract: We examined the expression of matrilysin mRNA in sporadic and hereditary colorectal adenomas to clarify the role of matrilysin in tumorigenesis. Matrilysin mRNA was not detected in normal colorectal mucosa from patients with either sporadic or familial adenomas. Matrilysin mRNA expression in sporadic adenomas correlated with the degree of dysplasia and the size of the mass, whereas most of the adenomas in patients with familial adenomatous polyposis coli expressed matrilysin mRNA irrespective of adenoma size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…Another potential marker for invasion might be MMP-7 -which is also known as matrilysin. Expression of this marker, namely, is found to be increased in high-grade dysplasia in colonic adenomas [15,33], and its suppression in vitro leads to inhibition of invasion by colon carcinoma cells [34]. Of particular interest in this connection is the fact that a working group headed by Kirchner has recently demonstrated that beta-catenin regulates the expression of MMP-7 [4].…”
Section: Vienna Classification: Advantages and Critical Pointscontrasting
confidence: 75%
“…Another potential marker for invasion might be MMP-7 -which is also known as matrilysin. Expression of this marker, namely, is found to be increased in high-grade dysplasia in colonic adenomas [15,33], and its suppression in vitro leads to inhibition of invasion by colon carcinoma cells [34]. Of particular interest in this connection is the fact that a working group headed by Kirchner has recently demonstrated that beta-catenin regulates the expression of MMP-7 [4].…”
Section: Vienna Classification: Advantages and Critical Pointscontrasting
confidence: 75%
“…Different studies showed that some MMP, including MMP2, MMP7 and MMP9 are expressed in colorectal adenomas that are well established premalignant lesions of colorectal cancers [18-20,42], implying their role other than extracellular matrix destruction and metastasis in cancer development and progression. The expression of E1AF, an Ets family transcriptional factor that plays a role in the progression of CRC, has been shown to be associated with the expression of MMP1 and MMP7 in CRC tissues [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that MMP3 could be implicated in tumor invasion, lymph node involvement and metastatic spread in CRC. MMPs are overexpressed in a variety of premalignant tumor tissues, including colorectal adenoma [18-20] and MMP7 has been shown to be important in the growth of early colonic adenomas and their transformation into invasive cancer [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that in patients with FAP, MMP-7 is constitutively overexpressed in all polyps, regardless of size or dysplasia, although this was not true in sporadic adenomas from non-FAP cases (22, 31). Our studies, however, for MMP-2 and MMP-9 activities in FAP colorectal samples showed a different pattern for these particular MMPs.…”
Section: Discussionmentioning
confidence: 85%